A Quest for Defining Terrorism in International Law: The Emerging Consensus (Journal of International Studies, 2020)
The United Nations (UN) has no internationally-agreed definition of terrorism. The definitional impasse has prevented the adoption of a Comprehensive Convention on International Terrorism. Even in the immediate aftermath of 9/11 the UN failed to adopt the Convention, and the deadlock continues to this day. The prime reason is the standoff with the Organization of the Islamic Conference (OIC). The Arab Terrorism Convention and the Terrorism Convention of the Organization of the Islamic Conference defines terrorism to exclude armed struggle for liberation and self-determination. This increased its complexity and vagueness. The aim of this paper is to examine the definitional aspect of terrorism and the challenges faced in adopting a single universally accepted definition by the international community. The methodology adopted in this paper is purely a library based research focusing mainly on primary and secondary sources. The paper concludes that nations or states have to come to agreement on a definition of the term â€œterrorismâ€, for without a consensus of what constitute terrorism, nations or states could not unite against it. A general definition of terrorism is necessary in order for the international community to fight against terrorism in a precise way.